O 'Jogo da Onça': Uma interlocução entre o cotidiano e o ensino de adição e subtração de números decimais - Lucas, Leandro Mário (2018)
This research analyzes the didactic-pedagogical contributions of 'O Jogo da Onça', adapted from the students' daily life, for the teaching of Addition and Subtraction of Decimal Numbers. Held in a public school in Paraiba, the qualitative approach is characterized by its exploratory and descriptive character and by following the presuppositions of the participant research. In the exploratory phase, we applied, in four classes of elementary school, two semistructured questionnaires, one of sociocultural nature and another of the survey type. The data they provided allowed us to identify the one who presented the most favorable dai ly routine for the game adaptation, the greatest difficulties and more everyday knowledge related to the content explored. In the participatory phase, the main pedagogical tool was the 'Game of the Onça', in its four adaptations, entitled "The Consumer and the Taxes", "Fox and the Chickens", "Dog and Goats" and Gasoline Prices". With these versions, we explore concepts related to decimal numbers and their addition and subtraction operations. To do so, we use four problems, which solutions should also be performed in the act of playing. At the moment, the researcher mediated the process from the students' everyday knowledge and their concerns about the challenges of the game. After the interventions, in order to analyze the evolution of learning, we applied a second survey test. The data he provided us, along with those collected during the exploratory and participatory phases, were analyzed in the light of D'Ambrósio etnomathematica (1986, 1996, 1998, 2015). Gambling and problem solving, in turn, are analyzed under multiple glances. However, in the first theme, we highlight the vision of Vigotski (2007, 2008), while in the second, the considerations of the National Curricular Parameters (BRASIL, 1998) and of Onuchic (2013) predominate. Finally, the theoretical and practical reflections allowed us to conclude that "Game da Onça", adapted from students' everyday life, awakened motivation and engagement, meant some representations and numerical orders and allowed to explore estimates, approximations and rounding. It also allowed us to awaken criticality, introduce, explore and solve problems related to the content explored, as well as made possible the evaluation of students and the formation of ethical, collaborative and socializing behaviors.